Teaching Note—Preparing Advanced Standing Students for Social Work Practice. (2nd October 2022) - Kourgiantakis, Toula; Sewell, Karen M.; Sanders, Jane; Craig, Shelley; Bogo, Marion
ABSTRACT: There have been longstanding debates about Master of Social Work (MSW) Advanced Standing programs. Many schools of social work offer Advanced Standing status to students with a Bachelor of Social Work (BSW) that allows students to enter directly into a concentrated and specialized second year of the MSW program. There are arguments that BSW programs are not equivalent to the foundational year of the MSW and do not adequately prepare students for entry into specialized programs and direct social work practice. This teaching note describes a bridging Advanced Standing Practice Seminar developed to prepare Advanced Standing students for competent direct social work practice using innovative teaching methods, such as simulation-based learning. Implications for social work education and practice are presented.